Menstrual health and hygiene among Juang women: a particularly vulnerable tribal group in Odisha, India - Prasanna Kumar Mudi; Manas Ranjan Pradhan; Trupti Meher (BMC, 2023)
Abstract Background Menstruation is a normal biological process that all women go through, yet it is shrouded in secrecy, taboos, and even stigma in many societies. Studies have shown that women from socially disadvantaged groups are more likely to have preventable reproductive health issues and have less understanding of hygienic menstrual practices. Therefore, this study aimed to provide an insight into the most sensitive issue of menstruation and menstrual hygiene practices among the women of the Juang tribe, recognized as one of the particularly vulnerable tribal groups (PVTG) in India. Methods A cross-sectional study using a mixed-method approach was carried out among Juang women in Keonjhar district of Odisha, India. Quantitative data was gathered from 360 currently married women to assess practices associated with menstruation and its management. In addition, 15 focus group discussions and 15 in-depth interviews were conducted to explore the views of Juang women on menstrual hygiene practices, cultural beliefs, menstrual problems, and treatment-seeking behaviour. Inductive content analysis was used to analyse the qualitative data, while descriptive statistics and chi-squared tests were used to analyse quantitative data. Results Most Juang women (85%) used old clothes as absorbents during menstruation. Distance from the market (36%), lack of awareness (31%), and high cost (15%) were cited as the contributing factors to the low level of sanitary napkin usage. Around 85% of women were restricted from participating in religious activities, and 94% avoided social gatherings. Seventy-one percent of the Juang women experienced menstrual problems, while only one-third of them sought treatment for their problems. Conclusion Hygienic practices during menstruation are far from satisfactory among Juang women in Odisha, India. Menstrual problems are common, and the treatment sought is insufficient. There is a need for awareness generation on menstrual hygiene, the adverse effects of menstrual problems, and the provision of low-cost sanitary napkins among this disadvantaged, vulnerable tribal group.